Is a Long Essay Always a Good Essay? The Effect of Text Length on Writing Assessment - Fleckenstein, Johanna; Meyer, Jennifer; Jansen, Thorben; Keller, Stefan; Köller, Olaf (Frontiers in Psychology, 2020)
The assessment of text quality is a transdisciplinary issue concerning the research areas of educational assessment, language technology, and classroom instruction. Text length has been found to strongly influence human judgment of text quality. The question of whether text length is a construct-relevant aspect of writing competence or a source of judgment bias has been discussed controversially. This paper used both a correlational and an experimental approach to investigate this question. Secondary analyses were performed on a large-scale dataset with highly trained raters, showing an effect of text length beyond language proficiency. Furthermore, an experimental study found that pre-service teachers tended to undervalue text length when compared to professional ratings. The findings are discussed with respect to the role of training and context in writing assessment.